Molecular characterization of interacting complexes and conjugates induced by the dry-state heating of β-lactoglobulin and sugar beet pectin. (June 2019) - Qi, Phoebe X.; Chau, Hoa K.; Hotchkiss, Arland T.
Abstract: To gain an understanding of the improved emulsion stability, exhibited by the Maillard-type reaction products consisted of whey protein isolate (WPI) and sugar beet pectin (SBP), we investigated the molecular properties of interacting complexes and conjugates formed between β-lactoglobulin (β-LG), the main protein of whey, and SBP. The reaction was carried out at varying mass ratios, β-LG:SBP = 1:0, 5:1, 3:1, 2:1, 1:1, and 0:1 through dry heating (60 °C, 79% RH, 72 h). The physiochemical properties of the products from the reaction were characterized by an online multi-detection (UV, dRI, MALLS, and DPV) HPSEC system. The results showed that although the molecular weight distribution and the shape of the SBP in each fraction was significantly transformed by heating alone, the overall apparent average weight-average molar mass ([Mw ]av ) and average intrinsic viscosity ([ηw ]av ) were not affected. Detailed analyses revealed about 29, 34, 44 and 56% of the total β-LG participated in the reactions and interactions with SBP for the mixture of 5:1, 3:1, 2:1, and 1:1 respectively. Furthermore, it was demonstrated that β-LG tends to interact with the group of SBP molecules with higher average weight-average molar mass [Mw ] (∼800 kDa) through local electrostatic and hydrophobic interactions. Combination of complexes and conjugates was formed between β-LG and intermediate sized SBP (∼125 kDa), and the shapes of these two classes of SBP molecules were maintained, i.e., a mixture of compact spheres, random coils, and rigid rods. The conjugates were developed by the chemical reactions between β-LG and the group of SBP with the lowest [Mw ] (∼100 kDa), leading to the products with altered molecular structures and increased chemical bond stiffness compared to that of SBP. Graphical abstract: Image 101441 Highlights: Dry heating altered the hydrodynamic properties not the [Mw ]av and [ηw ]av of SBP. Electrostatic and hydrophobic interacting complexes dominate the large [Mw ] species. Smaller SBP molecules [Mw ]∼100 kDa tend to form covalent conjugates with β-LG. Intermediate sized SBPs [Mw ]∼125 kDa are able to interact and conjugate with β-LG. The conjugates have more stiffened molecular structure than the unreacted SBP.